2020
DOI: 10.1111/adb.12934
|View full text |Cite
|
Sign up to set email alerts
|

Incubation of alcohol craving as it naturally occurs in a developmentally diverse sample of dependent and nondependent drinkers

Abstract: Longer periods of abstinence are shown to enhance response to alcohol cues among alcohol‐dependent animals and humans, a phenomenon described as “incubation of craving.” The present work examined the effects of days since last drink on general craving and alcohol‐cued craving as it occurs in daily life and explored whether effects were influenced by age and dependence. Three samples were combined to include 266 drinkers ranging in age from 14 to 67 years recruited from the community; about half (59.4%) met cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
1
8
0
1
Order By: Relevance
“…The present study aimed to (a) examine synergistic effects of cue exposure and alcohol exposure (i.e., postdrinking status) on craving in the natural environment and (b) test the extent to which these effects are moderated by individual differences in sensitivity to alcohol’s effects (Fleming et al, 2021; Trela et al, 2018). Consistent with findings from prior laboratory (e.g., de Wit & Chutuape, 1993; Kirk & de Wit, 2000; Litt & Cooney, 1999; Manchery et al, 2017; Monti et al, 1993; Ramirez et al, 2015a, 2015b) and field-based studies (Fatseas et al, 2015; Kuerbis et al, 2020; Miranda et al, 2014; Ramirez & Miranda, 2014; Schoenmakers & Wiers, 2010; Trela et al, 2018; Treloar Padovano & Miranda, 2021), craving in the natural environment was increased after cue exposure and during drinking episodes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present study aimed to (a) examine synergistic effects of cue exposure and alcohol exposure (i.e., postdrinking status) on craving in the natural environment and (b) test the extent to which these effects are moderated by individual differences in sensitivity to alcohol’s effects (Fleming et al, 2021; Trela et al, 2018). Consistent with findings from prior laboratory (e.g., de Wit & Chutuape, 1993; Kirk & de Wit, 2000; Litt & Cooney, 1999; Manchery et al, 2017; Monti et al, 1993; Ramirez et al, 2015a, 2015b) and field-based studies (Fatseas et al, 2015; Kuerbis et al, 2020; Miranda et al, 2014; Ramirez & Miranda, 2014; Schoenmakers & Wiers, 2010; Trela et al, 2018; Treloar Padovano & Miranda, 2021), craving in the natural environment was increased after cue exposure and during drinking episodes.…”
Section: Discussionsupporting
confidence: 84%
“…Interindividual variation in cue-induced craving is associated with in vivo alcohol consumption in the lab, supporting the utility of cue-induced craving as a proximal indicator of motivation to drink (e.g., MacKillop & Lisman, 2005; O’Malley et al, 2002). Other work shows that laboratory-measured cue-induced craving predicts alcohol use and problems outside of the lab (e.g., Papachristou et al, 2014; Ramirez & Miranda, 2014), and that cue exposure in the natural environment is associated with increased craving in daily life (e.g., Fatseas et al, 2015; Kuerbis et al, 2020; Miranda et al, 2014; Trela et al, 2018; Treloar Padovano & Miranda, 2021).…”
mentioning
confidence: 99%
“…To be consistent with laboratory conditions, our ecological analysis was restricted to times in daily life prior to consuming alcohol, thereby indexing conditioned craving outside of drinking episodes. Although our previous investigation of whether the association between alcohol cues and craving varied as a function of craving incubation (i.e., days since last alcohol use) and age did not find developmental differences in craving (Treloar Padovano & Miranda, 2021), that analysis did not incorporate real‐world peer contexts or laboratory data. In the current study, we expected that age would matter when considering a social‐context cue among youth and hypothesized that the relevance of the presence of peers for eliciting alcohol‐related craving would be heightened for younger participants in both laboratory and ecological settings.…”
Section: Discussionmentioning
confidence: 90%
“…First, intoxication‐related increases in alcohol demand following a laboratory alcohol challenge are associated with changes in craving across the blood alcohol concentration curve (Amlung et al, 2015). Second, studies using ecological momentary assessment have reported that exposure to alcohol cues in the natural environment is associated with craving in daily life (e.g., Kuerbis et al, 2020; Trela et al, 2018; Treloar Padovano & Miranda Jr, 2021). Collectively, these findings raise interesting questions about the ideal time frame for assessing acute levels of demand and craving.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for this conclusion comes from studies reporting that animals who received extended administrations of methamphetamine or morphine over time do not show heightened cue-elicited reinstatement of responding for those drugs when tested following extinction (Doherty et al, 2009;Rogers et al, 2008). However, other research found that increasing the duration of heroin self-administration in rats results in an escalation of reinstatement of responding by conditioned cues (Zhou et al, 2009). None of these studies have explored EtOH self-administration or used behavioral economic tasks.…”
Section: Discussionmentioning
confidence: 99%